Sensitive Kinetic-Spectrophotometric Determination of Protein Based on its Inhibitive Effect on the Decolorization of Dibromo-p-methylsulfonazo - Yu, Hui; Zhai, Qing-Zhou; Hu, Wei-Hua; Xiang, Song-Bai (Asian Journal of Chemistry, 2011)
A novel kinetic spectrophotometric method for the determination of protein is developed on the basis of kinetic effect of bovine serum albumin (BSA) on the inhibitory effect on the oxidation reaction of dibromo-p-methylsulfonazo by potassium periodate. The absorbance differences (DA) between inhibitive and non-inhibitive systems are maximum at 558 nm. The absorbance difference is linearly related with the concentration of bovine serum albumin over the range of 5.0-55.0 μg/mL and fitted the equation: DA = 8.988 × 10-3 C (C: μg/mL) + 0.0185, with a regression coefficient of 0.9960 at the wavelength. The detection limit of the method was 1.55 μg/mL. The method was used to determine protein in pure milk. The relative standard deviation was 1.58 and 1.49 % for 13 replicate determinations. The recovery of the standard addition was 101.1 and 99.33 %.